Discrete-time H∞ control of a class of underactuated electromechanical systems - Hafeez, Y. (Institute of Electrical and Electronics Engineers Inc., 2017)
This paper focuses on the design and performance of sampled-data robust control of a class of continuous-time underactuated electromechanical systems. The control law is designed on the philosophy based on stabilization of discrete-time equivalent model of a continuous-time system which can be broadly classified into sampled-data stabilization of a class of underactuated linear systems with a time-varying actuation characteristics. The system can be actuated by a short duration pulse in a fixed interval of time. The system is discretized for complete actuation cycle to get an equivalent discrete-time model of the continuous-time system. The equivalent model is developed by considering a complete actuation cycle as a single discrete step. The continuous-time system is fully actuated in this interval and unactuated otherwise. The state feedback control law is designed on the basis of fully actuated, time invariant exact discrete-time equivalent model of the continuous-time system. The simulations show that proposed controller achieved the desired orientation control. © 2016 IEEE.